Enhanced piezoelectric properties of aluminium doped zinc oxide thin film for surface acoustic wave resonators on a CMOS platform - Md Ralib, Aliza Aini; Mortada, Ossama; Orlianges, Jean Christophe; Crunteanu, Aurelian; Chatras, Matthieu; Nordin, Anis Nurashikin (Springer New York LLC, 2017)
The increase in frequency spectrum for wireless communication system has led to the growing interest in thin film electroacoustic technology that scales favorably upon miniaturization. Non-ferroelectric piezoelectric thin films such as Zinc Oxide is one of the most promising material for Complementary Metal Oxide Semiconductor-Microelectromechanical system (CMOS-MEMS) integration due to its silicon compatibility and good piezoelectric properties. This paper compares ZnO and Al doped ZnO (AZO) thin films performance characteristics when applied as CMOS-based surface acoustic wave (SAW) resonators. The interdigitated electrodes were fabricated using 0.35 μm CMOS technology followed by piezoelectric thin film deposition and probe pad patterning. Pure ZnO and AZO with 2 wt% Al2O3 have been prepared by pulse laser deposition and RF magnetron sputtering respectively. Both deposited ZnO and AZO thin films exhibited preferential crystalline growth in 002 direction. EDS analysis confirmed the incorporation of aluminium in zinc oxide thin films. High frequency electrical measurement results revealed that the devices with AZO thin film have enhanced performances as compared to devices based on ZnO thin film. It is shown that the insertion loss for AZO thin film was reduced from −65.1 to −53.5 dB and the quality factor was enhanced from 11.33 to 25.81. More significantly, the electromechanical coupling coefficient and piezoelectric coefficient were enhanced from κ = 0.044–0.069% and d31 = 5.00 to 5.41 pm/V for AZO devices compared to those based on ZnO devices, respectively. One possible explanation of these enhanced piezoelectric properties comes from the almost ideal c-axis orientation of AZO thin film as compared to pure ZnO thin films. Our results suggest that the AZO thin film can be a better candidate for surface acoustic wave resonator using the CMOS-MEMS platform.